Perancangan Prototype Sistem Informasi Monitoring Stok Barang pada PT XYZ - Martono (Jurnal PROCESSOR, 2021)
Monitoring is one of the important stages that must be carried out regularly, especially on the stock of goods. With the continuous monitoring process, it is hoped that all goods will always be under supervision so that stock management becomes easier and more accurate. PT XYZ at this time, in monitoring the stock of goods, they still use general applications that are devoted to calculating numbers, resulting in the current stock of monitoring system having several shortcomings, namely the unavailability of the login function and reports that must be reprocessed with the different application. Based on these problems, the authors conducted a research entitled designing a prototype monitoring stock of goods information system at PT XYZ. The information system that built in this study will be defined using the waterfall modeling and use case diagrams. The final result of this research is a prototype of an stock of monitoring information system that allows system users to carry out various functions such as functions to change their own passwords, perform CRUD management of user data, item data, category data, brand data, unit data, vehicles data, supplier data, incoming goods data, outgoing goods data and processing reports that related to the stock of goods at PT XYZ.